Georgians and Iranians in Each other's Notion - Bartaia, Nomadi (Actual Problems of Kartvelology, 2025)
Throughout its long history, Iran as a whole has had and continues to have independent statehood three times, once during the Achaemenid period (5th-3rd centuries BC), secondly during the Sassanid period (3rd-7th centuries BC), and thirdly since the Safavid period (16th-18th centuries) to the present day. All three times, the eastern part of Georgia was under the political influence of Iran. Although the political relations between Iran and Georgia were not permanent, it can be said that relations in the cultural sphere between these two countries have always existed in different eras and in various forms. We were interested in how Georgians and Iranians perceived each other historically. The work consists of two parts. The first part will review the perceptions of Iranians about Georgians, and the second, on the contrary, Georgians about Iranians.